Potential of lacto-N-biose I as a prebiotic for infant health: A review - Kiyat, Warsono El; Astuti, Santi Dwi; Budijanto, Slamet; Syamsir, Elvira (Communications in Science and Technology, 2021)
Prebiotic is one alternative in the prevention of disease in infants. Generally, it is available as oligosaccharide which may occur naturally, but can also be added as a dietary supplement for food, beverage or formula. Lacto-N-biose I (LNB), a kind of prebiotic has not been widely examined in regard to its activities as a bifidogenic factor. Naturally, it is available in a compound form in human milk oligosaccharide (HMO) as the main constituent of human milk rather than fat and protein. HMOs also have prebiotic activity in the body and play an important role in providing nutrition for the infant health. LNB is potential to be used in food ingredient, especially infant food formula regarding the prebiotic effect and it could be enzymatically synthesized using enzymes involved in the LNB biosynthesis pathway by microorganisms.